Magnitudes and capital key divergence of the Eurosystem's PSPP/PEPP purchases - Update December 2020 - Annika Havlik; Friedrich Heinemann (ZEW - Leibniz Centre for European Economic Research, 2020)
Since March 2020, the Eurosystem has been purchasing government bonds under the Pandemic Emergency Purchase Programme (PEPP). The PEPP was set up as a non-standard policy measure to encounter the economic and financial consequences of the Covid-19 pandemic and is an additional program to the ongoing Public Sector Purchase Programme (PSPP). This study updates the quantitative analysis by Havlik and Heinemann (2020) with a focus on the Eurosystem's PSPP and PEPP transactions since the outbreak of the pandemic. With respect to the PSPP/PEPP purchases made between March and September 2020, this expertise assesses the size of purchase flows and stocks, country allocations and their magnitude relative to this year's projected government deficits. Moreover, we assess the speed of purchases in light of the current existing envelopes.
Additional information: Study supported by the Brigitte Strube Foundation
Keywords: 330